Eighteen Months Follow-Up with Patient-Centered Outcomes Assessment of Complete Dentures Manufactured Using a Hybrid Nanocomposite and Additive CAD/CAM Protocol - Cristache, Corina Marilena; Totu, Eugenia Eftimie; Iorgulescu, Gabriela; Pantazi, Aida; Dorobantu, Dorel; Nechifor, Aurelia Cristina; Isildak, Ibrahim; Burlibasa, Mihai; Nechifor, Gheorghe; Enachescu, Marius (MDPI, 2020)
The present study aimed to assess the eighteen month follow-up patient-centered outcomes of a simple and predictable protocol for 3D-printed functional complete dentures manufactured using an improved poly(methyl methacrylate) (PMMA)-nanoTiO(2). A detailed morphological and structural characterization of the PMMA-TiO2 nanocomposite, using SEM, EDX, XRD, and AFM, after 3D-printing procedure and post-wearing micro-CT, was also performed. Methods: A total of 35 fully edentulous patients were enrolled in this prospective study. A 0.4% TiO2-nanoparticle-reinforced PMMA composite with improved mechanical strength, morphologically and structurally characterized, was used according to an additive computer-aided design and computer-aided manufacturing (CAD/CAM) protocol for complete denture fabrication. The protocol proposed involved a three-step appointment process. Before denture insertion, 1 week, 12 month, and 18-month follow up patients were evaluated via the Visual Analogue Scale (VAS, 0-10) and Oral Health Impact Profile for Edentulous Patients (OHIP-EDENT), with a higher score meaning poor quality of life. Results: A total of 45 complete denture sets were inserted. OHIP-EDENT scored significantly better after 18 months of denture wearing, 20.43 (+/- 4.42) compared to 52.57 (+/- 8.16) before treatment; mean VAS was improved for all parameters assessed. Conclusions: Within the limitations of this study, we can state that the proposed workflow with the improved material used is a viable treatment option for patients diagnosed with complete edentulism.
Keywords: PMMA-nanotitania composite; OHIP-EDENT; digital light processing; complete denture; quality of life; POLY(METHYL METHACRYLATE); CHEMICAL CHARACTERISTICS; NANOINDENTATION; ADAPTATION; General & Internal Medicine